If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5a + -4) = 132 Reorder the terms: -3(-4 + 5a) = 132 (-4 * -3 + 5a * -3) = 132 (12 + -15a) = 132 Solving 12 + -15a = 132 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -15a = 132 + -12 Combine like terms: 12 + -12 = 0 0 + -15a = 132 + -12 -15a = 132 + -12 Combine like terms: 132 + -12 = 120 -15a = 120 Divide each side by '-15'. a = -8 Simplifying a = -8
| x=-7+4y(1.5) | | 8m-5n=5m+7 | | 6x+20=4x+13 | | log(y)=9t-4 | | 76=x^3+3*x | | 8x+2=7(x-2)+4 | | 15x-12y=141 | | 8+40n-35=-307 | | 4x+72=3x+36 | | 2P=q+5 | | -7+4y-2y+4=0 | | 10=a(43)(3) | | 16+11h=7+9+11h | | -11+13v-19v=3-8v | | -20+7t=-13+7t+2 | | x^2+7x-5= | | 0.5x+x=4.75 | | 5x+118+3x+126= | | 10k-5=-3+10k-2 | | -1/2k=3/4k-3 | | 5.8=-logarithm(Ka) | | -7+6n=7+6n | | -15-9+13p=-13+14p | | y=kx+5 | | F(x)=15x-8 | | 5(5x-4)+11=-3 | | 7-3m=40 | | c+14c+11=7c-13 | | -2(0)+1=5-2(0) | | 2m-8=19-m | | 2(3d+c)-(4d+2c)= | | -2f=2+1-2f |